2010
DOI: 10.1371/journal.pone.0011520
|View full text |Cite|
|
Sign up to set email alerts
|

CD40: Novel Association with Crohn's Disease and Replication in Multiple Sclerosis Susceptibility

Abstract: BackgroundA functional polymorphism located at −1 from the start codon of the CD40 gene, rs1883832, was previously reported to disrupt a Kozak sequence essential for translation. It has been consistently associated with Graves' disease risk in populations of different ethnicity and genetic proxies of this variant evaluated in genome-wide association studies have shown evidence of an effect in rheumatoid arthritis and multiple sclerosis (MS) susceptibility. However, the protective allele associated with Graves'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…This finding therefore suggests that the linked causal variants in these regions are likely to be expression quantitative trait loci (eQTL), at which polymorphism affects the expression of one or more transcripts. Indeed, the data obtained on candidate genes for several autoimmune diseases strongly support the hypothesis that most of the genetically encoded risk of disease is conferred by eQTL [38,71,103,[156][157][158][159][160][161][162][163].…”
Section: From Genes To Functionmentioning
confidence: 67%
“…This finding therefore suggests that the linked causal variants in these regions are likely to be expression quantitative trait loci (eQTL), at which polymorphism affects the expression of one or more transcripts. Indeed, the data obtained on candidate genes for several autoimmune diseases strongly support the hypothesis that most of the genetically encoded risk of disease is conferred by eQTL [38,71,103,[156][157][158][159][160][161][162][163].…”
Section: From Genes To Functionmentioning
confidence: 67%
“…The CD40 SNPs rs1883832 and rs4810485 have been identified as susceptibility markers for this and other autoimmune diseases, such as GD (Tomer et al, 2002;Kim et al, 2003;Li et al, 2012), MS (Blanco-Kelly et al, 2010;Sokolova et al, 2013), and SLE (Vazgiourakis et al, 2011;Chen et al, 2015;Lee et al, 2015). In addition, several studies suggest that these polymorphisms affect CD40 expression at the mRNA and protein level (Jacobson et al, 2005;Vazgiourakis et al, 2011;Field et al, 2015;Wagner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other non-HLA risk loci for RA, including the CD40 gene, have been identified based on genome-wide association studies and meta-analysis (Wellcome Trust Case Control Consortium, 2007;Raychaudhuri et al, 2008;Perricone et al, 2011;Suzuki et al, 2011). Interestingly, CD40 has been implicated in other autoimmune diseases, such as multiple sclerosis [MS; Australia and New Zealand Multiple Sclerosis Genetics Consortium (ANZgene), 2009], Grave's disease (GD; Li et al, 2012), systemic lupus erythematosus (SLE; Vazgiourakis et al, 2011), and Crohn's disease (Blanco-Kelly et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies reported that CTLA4 may also influence the risk of developing CD [15,16]. Moreover, in a Spanish meta-analysis, the frequency of the minor allele rs1883832T of the CD40 gene was observed to be significantly higher in CD patients than that in control individuals, but it was not significantly higher in UC patients [17].…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 95%